Neuromuscular, endocrine, and perceptual fatigue responses during different length between-match microcycles in professional rugby league players - McLean, B. D.; Coutts, A. J.; Kelly, V.; McGuigan, M. R.; Cormack, S. (International Journal of Sports Physiology and Performance, 2010)
Introduction: The purpose of this study was to examine the changes in neuromuscular, perceptual and hormonal measures following professional rugby league matches during different length between-match microcycles. Methods: Twelve professional rugby league players from the same team were assessed for changes in countermovement jump (CMJ) performance (flight time and relative power), perceptual responses (fatigue, well-being and muscle soreness) and salivary hormone (testosterone [T] and cortisol [C]) levels during 5, 7 and 9 d between-match training microcycles. All training was prescribed by the club coaches and was monitored using the session-RPE method. Results: Lower mean daily training load was completed on the 5 d compared with the 7 and 9 d microcycles. CMJ flight time and relative power, perception of fatigue, overall well-being and muscle soreness were significantly reduced in the 48 h following the match in each microcycle (P < .05). Most CMJ variables returned to near baseline values following 4 d in each microcycle. Countermovement jump relative power was lower in the 7 d microcycle in comparison with the 9 d microcycle (P < .05). There was increased fatigue at 48 h in the 7 and 9 d microcycles (P < .05) but had returned to baseline in the 5 d microcycle. Salivary T and C did not change in response to the match. Discussion: Neuromuscular performance and perception of fatigue are reduced for at least 48 h following a rugby league match but can be recovered to baseline levels within 4 d. These findings show that with appropriate training, it is possible to recover neuromuscular and perceptual measures within 4 d after a rugby league match.